Indonesia's National Capital Relocation Policy: An Analysis of Political Support in Parliament and the Public Responses on Twitter - Ikfina, Muhammad Ulfi (Universitas Muhammadiyah Yogyakarta, 2024)
This study aims to explain the policy of relocating Indonesia's capital city from the perspective of political support in parliament and public response on Twitter. This research used a qualitative method with a case study approach. The findings revealed that the policy of relocating the National Capital (IKN) in quantity has received dominant political support in parliament. Eight of the nine political parties with parliament seats agreed to approve the policy. However, at the beginning of the plan to relocate the national capital, the government, as the initiator of the approach, has yet to gain political support in parliament and has minimal communication with the public. Thus, the relocating policy caused a powerful polemic among the people, even in the vortex of the parliamentary elite. Interestingly, the public response on Twitter, content, and narratives turned predominantly positive after circulating explanations from the government regarding the policy. So, public policy and communication are closely related; both must go hand in hand.